Effect of climate warming on the grain quality of early rice in a double-cropped rice field: A 3-year measurement - Wang, Yong; Yang, Taotao; Xiong, Ruoyu; Zeng, Yanhua; Zhang, Jun; Tang, Feiyu; Zeng, Yongjun; Huang, Shan (Frontiers in Sustainable Food Systems, 2023)
Introduction The threat of climate warming to global rice production has been widely addressed, but little is known about its influence on the quality of rice grains. Methods A free-air temperature increase (FATI) facility with two widely-planted high-quality cultivars was used to explore the impact of warming on the grain quality of early rice in subtropical China over 3 consecutive years. Results Compared with the control, FATI increased diurnal canopy temperature by 1.5°, and thus, rice growth duration was shortened by 4.0 d under warming. We found that warming significantly reduced both the milled rice and head rice rates relative to the control, thereby leading to a decrease in the milled rice and head rice yield by 3.9 and 8.3%, respectively. The chalky grain rate and chalkiness were increased by 19.1 and 22.2% under warming compared with the control, respectively. The content of protein, essential amino acids, and non-essential amino acids were increased by 4.1, 5.4, and 4.9% under warming, respectively. Warming reduced the amylose content and setback by 2.0 and 47.5% but increasing peak viscosity, trough viscosity, breakdown, and final viscosity by 9.5, 13.6, 5.7, and 6.0%, respectively. Conclusion Our results suggest that the deteriorated milling and appearance quality induced by warming may be an upcoming challenge for high-quality early rice production in the future.